Comprehensive Survey of the Litter Bacterial Communities in Commercial Turkey Farms - Adhikari, Bishnu; Tellez-Isaias, Guillermo; Jiang, Tieshan; Wooming, Brian; Kwon, Young Min (Frontiers in Veterinary Science, 2020)
The importance of microbiota in the health and diseases of farm animals has been well documented for diverse animal species. However, studies on microbiotas in turkey and turkey farms are relatively limited as compared to other farm animal species. In this study, we performed a comprehensive survey of the litter microbiotas in 5 commercial turkey farms in the Northwest Arkansas (H, M, V, K, and R farms) including one farm with positive incidence of cellulitis (R farm). Altogether 246 boot swabs were used for 16S rRNA gene profiling of bacterial communities. At phylum level, 11 major bacterial phyla (≥ 0.01%) were recovered. At genus level, 13 major bacterial genera were found whose relative abundance were ≥ 2%. The microbial composition at both phylum and genus levels as well as their diversities varied across different farms, which were further affected by different flocks within the same farms and the ages of turkeys. Generally, the Firmicutes were higher in the flocks of younger birds, while the Actinobacteria and Bacteroidetes were higher in the flocks of the older birds. The Proteobacteria were highly enriched (47.97%) in K farm housing 56-day-old turkeys (K-56), but Bacteroidetes were found the highest in the flock C of M farm housing 63-day-old turkeys (M-C-63; 22.38%), followed by K-84 group (17.26%). Four core bacterial genera (Staphylococcus, Brevibacterium, Brachybacterium, and Lactobacillus) were identified in all samples except for those from R farm. In contrast, 24 core bacterial genera were found based in all cellulitis-associated samples (R farm), including Corynebacterium, an unknown genus of family Bacillaceae, Clostridium sensu stricto 1 (> 97% similarity with C. septicum), and Ignatzschineria among others, suggesting their possible roles in etiopathogenesis of cellulitis in turkeys. Overall results of this study may provide valuable foundation for future studies focusing on the role of microbiota in the health and diseases of turkeys.